2021
DOI: 10.1111/1759-3441.12319
|View full text |Cite
|
Sign up to set email alerts
|

Does Government Ideology Affect the Relationship Between Government Spending and Economic Growth?

Abstract: This study examines whether government ideology affects the relationship between government spending and economic growth in eighty eight countries from 1975 to 2017 using dynamic panel estimators. Previous studies have overlooked the role of government ideology, which can influence economic policies such as government spending. The results show that government spending is negative and significant to economic growth, while left‐wing governments are associated with economic growth. However, when moderating for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Also, increasing government spending can lead to a more inefficient allocation of resources since governments tend to be less effective in spending money, while higher public spending can crowd‐down domestic credit. Our results are in line with Purewal and Haini (2022) and Haini and Loon (2021), who argued that financial development is a positive contributor to growth while government spending has a negative impact. The estimated coefficients for the stock market index ( finmar ) are significant and positive with the exception of the model with government debt (Model V).…”
Section: Resultssupporting
confidence: 92%
“…Also, increasing government spending can lead to a more inefficient allocation of resources since governments tend to be less effective in spending money, while higher public spending can crowd‐down domestic credit. Our results are in line with Purewal and Haini (2022) and Haini and Loon (2021), who argued that financial development is a positive contributor to growth while government spending has a negative impact. The estimated coefficients for the stock market index ( finmar ) are significant and positive with the exception of the model with government debt (Model V).…”
Section: Resultssupporting
confidence: 92%
“…On the empirical front, Kabuga and Ismail (2018) and Das and Paul (2011) found that trade openness stimulates the economic growth of 12 Emerging Asian economies. Haini and Wei Loon (2022) and Haini and Loon (2021) confirm these findings for ASEAN and OECD economies where trade induces economic growth. Similarly, Malefane and Odhiambo (2018) found a positive impact of trade openness on economic growth in South Africa, but the effect turns insignificant when geography and country size are considered.…”
Section: Trade Openness and Economic Growthsupporting
confidence: 68%
“…Volume 1, Issue 2 Winter / Spring 2024 economy (Haini & Wei Loon, 2021). The literature on FDI research is not particularly contentious since economists agree that FDI advances the receiving nation's technological development and, ultimately, its economic growth.…”
Section: International Journal Of Social Science Technology and Econo...mentioning
confidence: 99%